Aire Gene Influences the Length of the 3′ UTR of mRNAs in Medullary Thymic Epithelial Cells - Oliveira, Ernna H.; Assis, Amanda F.; Speck-Hernandez, Cesar A.; Duarte, Max Jordan; Passos, Geraldo A. (Frontiers in Immunology, 2020)
Aire is a transcriptional controller in medullary thymic epithelial cells (mTECs) modulating a set of peripheral tissue antigens (PTAs) and non-PTA mRNAs as well as miRNAs. Even miRNAs exerting posttranscriptional control of mRNAs in mTECs, the composition of miRNA-mRNA networks may differ. Under reduction in Aire expression, networks exhibited greater miRNA diversity controlling mRNAs. Variations in the number of 3'UTR binding sites of Aire-dependent mRNAs may represent a crucial factor that influence the miRNA interaction. To test this hypothesis, we analyzed through bioinformatics the length of 3'UTRs of a large set of Aire-dependent mRNAs. The data were obtained from existing RNA-seq of mTECs of wild type or Aire-knockout (KO) mice. We used computational algorithms as FASTQC, STAR and HTSEQ for sequence alignment and counting reads, DESEQ2 for the differential expression, 3USS for the alternative 3'UTRs and TAPAS for the alternative polyadenylation sites. We identified 152 differentially expressed mRNAs between these samples comprising those that encode PTAs as well as transcription regulators. In Aire KO mTECs, most of these mRNAs featured an increase in the length of their 3'UTRs originating additional miRNA binding sites and new miRNA controllers. Results from the in silico analysis were statistically significant and the predicted miRNA-mRNA interactions were thermodynamically stable. Even with no in vivo or in vitro experiments, they were adequate to show that lack of Aire in mTECs might favor the downregulation of PTA mRNAs and transcription regulators via miRNA control. This could unbalance the overall transcriptional activity in mTECs and thus the self-representation.